OPTIMALISASI LAMA PEMANFAATAN AREA TEPI DANAU BUATAN SEBAGAI FASILITAS REKREASI DI LINGKUNGAN PERUMAHAN - Alifiani, Amalia; Supriyadi, Bambang; Prianto, Eddy; Irawanto, Bambang (MATEMATIKA, 2014)
Much residential built by developers who are equipped with an artificial lake as its attractiveness. Recreation area in a residential environment promotes the maintenance of security and generally are closed. Likely users recreation area is a internal residential community and has more the long term to do recreation activities. To take advantage of the length time of community recreation activities it could take effective visit, but in fact the use of recreation area on the time of artificial lake tends to be limited due to security In this paper to determine the optimal value of long utilization of the limited time constrains of use for users from within and outside the housing. Linear Programming method to use for analysis the three approach maximal visit time from deferent time, visit time 12 our, 15 our and 24 our, obtained the higher of visitation time the longer utilization.The users most optimal to use recreation area the community from internal residential because it is influenced by environment.